Análise econômica da produção do Maracujazeiro amarelo em sistemas orgânico e convencional - Motta, Ivo de Sa; Degasperi da Cunha, Flavio Antonio; Alves de Sena, Jose Ozinaldo; Clemente, Edmar; Caldas, Rafael Granzioli; Lorenzetti, Emi Rainildes [UNESP] (Universidade Federal de Lavras (UFLA), 2008)
This work was carried out in the city of Maringa, located in the Northwest region of Parana, with the aim of analyzing economically the yellow passion fruit crop (Passiflora edulis Sims. f. flavicarpa Deg.), comparing organic and conventional production systems. To estimate technical coefficients, planting and production costs, and profitability indicators of culture, the data were surveyed from technicians of the region and based in experimental work, carried out at the Experimental Farm of lguaterm from the Maringa State University, in the period of june/2002 to july/2004. The total production costs of the culture in two agricultural years reached a value 12.94% higher for the conventional system, and in this same period the medium index of profitability was 21.39% higher for the organic system. The organic production system was economically feasible and provided a larger index of profitability.
Economical analysis of yellow passion fruit (Passiflora edulis Sims. f. flavicarpa Deg.) production in organic and conventional systems
Keywords: Passiflora edulis f. flavicarpa; production costs; index of profitability; crop systems